2016
DOI: 10.1016/j.virusres.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Cellular entry of the porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea virus (PEDV), a coronavirus discovered more than 40 years ago, regained notoriety recently by its devastating outbreaks in East Asia and the Americas, causing substantial economic losses to the swine husbandry. The virus replicates extensively and almost exclusively in the epithelial cells of the small intestine resulting in villus atrophy, malabsorption and severe diarrhea. Cellular entry of this enveloped virus is mediated by the large spike (S) glycoprotein, trimers of which mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
144
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 85 publications
2
144
0
3
Order By: Relevance
“…However, how the sialic acid binding activity affects the tropism of these alphacoronaviruses remains unclear. The S protein N-domain of some PEDV strains were thought to be dispensable for replication of PEDV in vitro [4446]. The large deletions in the S protein of the PEDV variants in this study indicated that this domain might also be dispensable in vivo .…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…However, how the sialic acid binding activity affects the tropism of these alphacoronaviruses remains unclear. The S protein N-domain of some PEDV strains were thought to be dispensable for replication of PEDV in vitro [4446]. The large deletions in the S protein of the PEDV variants in this study indicated that this domain might also be dispensable in vivo .…”
Section: Resultsmentioning
confidence: 70%
“…Besides, the mutant strain PC177-P2 can propagate well and induce diarrhea in piglets [43]. A deletion of 215 aa (position 19–233) in the N-terminal domain of the S protein analogous to the deletion observed in the variants revealed a not impaired propagation of PEDV in vivo [44]. Moreover, only variants with large S deletions were found in the field sample JAo-56, which indicated that the variants were able to independently propagate well in pigs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations